2021
DOI: 10.2147/ndt.s315572
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Treatment Reduced the Risk of Coronary Heart Disease in Patients with Depression: A Propensity-Score Matched Cohort Study

Abstract: Background: Major depressive disorder is a significant public health concern, which often leads to loss of productivity, functional decline, and various complications. The aim of this study was to investigate the effectiveness of acupuncture in the risk reduction of coronary heart disease (CHD) in patients with depression. Methods: We enrolled patients diagnosed with depression between January 1, 1997, and December 31, 2010, through the Taiwanese National Health Insurance Research Database (NHIRD). Propensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…12 Chinese medicine is an Eastern-style integrative intervention that usually involves the use of Chinese herbs and acupuncture. 13 A meta-analysis showed that acupuncture could potentially improve the Hasegawa Dementia Scale (HDS), Mini-Mental State Examination scores (MMSE), and Scale for the differentiation of syndromes of vascular dementia (SDSVD) in patients with vascular dementia. 14 Compared to those treated for Alzheimer's disease with Western medicine, patients in the acupuncture cohort were found to achieve preservation of their activities of daily living (ADL).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Chinese medicine is an Eastern-style integrative intervention that usually involves the use of Chinese herbs and acupuncture. 13 A meta-analysis showed that acupuncture could potentially improve the Hasegawa Dementia Scale (HDS), Mini-Mental State Examination scores (MMSE), and Scale for the differentiation of syndromes of vascular dementia (SDSVD) in patients with vascular dementia. 14 Compared to those treated for Alzheimer's disease with Western medicine, patients in the acupuncture cohort were found to achieve preservation of their activities of daily living (ADL).…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 99% of Taiwanese individuals have been covered by the NHIRD. 13 In other words, the NHIRD is a large-scale, long-term follow-up healthcare database. All medical services from both Western and Chinese physicians are recorded in the NHIRD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 In Taiwan, Chinese medical intervention services are also reimbursed by the NHI, including acupuncture therapy. 9 Treatment for neurological problems is the major reason that Taiwanese people seek acupuncture. 10 Almost half of dementia patients in Taiwan have experience receiving Chinese medical treatment.…”
Section: Introductionmentioning
confidence: 99%